CLINICAL SIGNIFICANCE OF THE VEGFR-2 IN THE TUMORS AND BLOOD SERA OF THE BREAST CANCER PATIENTS - E. A. Kim; A. M. Platova; I. V. Visotzkaya; E. S. Gershteyn; V. P. Letyagin; N. E. Kushlinskiy; E. E. Mironova (Опухоли женской репродуктивной системы)
The analysis of the changes of the content of the angiogenic factor VEGFR-2 in the cytosol of the tumor and blood sera of the 30 breast can- cer patients determined by immunoenzyme method during neoadjuvant therapy is given. Likewise the correlation of this index with the main clinicomorphological characteristics of the disease is assessed. The obtained results suggest on the possibility of the use of VEGFR-2 as the one of the diagnostic markers of the breast cancer. The index dynamics didn’t depend on the given therapy type but nonetheless the correlation of the VEGFR-2 content in the residual tumor after preoperative therapy with the grade of the treatment pathomorphosis is determined.